Education Intervention Guideline on Knowledge and Self-Care Practice for Women With Vulvovaginities (International Journal of Studies in Nursing, 2019)
Background Bacterial vaginosis (BV) is the most common vaginal infection affecting women of reproductive age (15-49 years of age). 5-8% of women with acute infection experience recurrent vulvo-vaginal candidiasis. Side effects of vaginitis can affect other aspects of health, which could be prevented by promoting a healthy related to vaginal health. Aim of the study. The aim of the present study was to evaluate the Education intervention guideline on knowledge and self-care practice for women with vulvovaginities. Design: A quasi- experimental design was adopted in the current study. Sample: A purposive sample of (130) women's were included in the current study. Setting: the current study was conducted at outpatient clinic affiliated at obstetric department at Benha University Hospital. Data collection: Two tools were used for data collection, first, interviewing questionnaire to collect data about the women' socio demographic characteristics and women's knowledge regarding vulvovaginities as definition, risk factors, complication, second tool, Self-Care Assessment Structured Interviewing Schedule as (Clean genital area after each toilet, dry after cleanliness) Results: the result of the present study should that the total knowledge was improved from (9.2%) at pre intervention to (86.2%) at post intervention phase. In addition there was demonstrates that, 87.7% of the women had an unsatisfactory level of self-care practices before the educational intervention. Meanwhile, after the educational intervention, 75.4% of them got a satisfactory level of self-care practices. Conclusion: Educational intervention was effective in improving the women's knowledge and self-care practices regarding vulvovaginities. Recommendations: Provide different educational programs regarding knowledge and self-care practice for women with vulvovaginities at different female health care settings.